Probiotic Lactiplantibacillus plantarum Probio87 Improves Gut Microbial Profiles in HPV-Positive Women: A Randomized, Placebo-Controlled and Double-Blind Study - Pei, Xu; Mageswaran Uma, Mageswary; Azka Ainun, Nisaa; Sarah, Binti Samsudin; Nurul Izza, Mohamed Rusdi; Abigail Rembui, Jerip; Chern Ein, Oon; Salina, Sany; Cheng Siang, Tan; Zhen-Hua, Zhu; Min Tze, Liong (Wiley, 2025)
HPV infection is a major global health concern, and recent evidence suggests that the gut microbiota may play a critical role in HPV progression and clearance. This study aimed to evaluate the modulatory effects of the probiotic strain Lactiplantibacillus plantarum Probio87 on the gut bacterial composition of HPV-positive women. A 12-week randomized, placebo-controlled trial was conducted in accordance with the Declaration of Helsinki, with ethical approval from the Medical Research and Ethics Committee, Ministry of Health Malaysia (NMRR-21-1819-61300), and registration at ClinicalTrials.gov (NCT05316064). Probiotic supplementation with L. plantarum Probio87 significantly modulated the gut microbiota. Specifically, reductions were observed in the relative abundance of potentially pathogenic bacteria, including Gardnerella vaginalis (p = 0.055), Fannyhessea vaginae (p = 0.039), and Bilophila species (p = 0.008). Conversely, levels of beneficial microbes such as L. plantarum (p = 0.001), Anaerotignum lactatifermentans (p = 0.039), Blautia faecis (p = 0.061), and Roseburia hominis A2-183 (p = 0.052) were elevated. These findings suggest that L. plantarum Probio87 promotes gut microbial balance by reducing dysbiosis-associated bacteria and enhancing beneficial populations. This modulation may contribute to improved vaginal and overall health in women with HPV infection.